De Nomine Rhythmi. Aspects of a Mythographical Excerpt among Etymology, Music, and Metrics (ACME, 2025)
This paper proposes, starting from a detailed analysis of the mythological contents exposed in the tenth chapter of the so-called Fragmentum Censorini (= Nikokrates, FGrHist and BNJ2 376 F 4), a new contextualisation of the excerpt within Pseudo Censorinus’ musical and metrical doctrine.
Keywords: Pseudo Censorinus; Nikokrates; Perimedes of Argos; Greek Epic Poetry; Heroic Hexameter